Ответы и объяснения

2012-10-09T16:40:28+04:00

1) y=\frac{2x}{3}*\sqrt{x}-2x;

y'=\frac{2\sqrt{x}}{3}+\frac{2x}{3}*\frac{1}{2\sqrt{x}}-2 ;

\frac{2\sqrt{x}}{3}+\frac{2x}{3}*\frac{1}{2\sqrt{x}}-2=0 ;

\frac{2\sqrt{x}}{3}+\frac{2x}{6\sqrt{x}}-2=0[tex];</p>&#10;<p>[tex]\frac{12x+6x-36\sqrt{x}}{18\sqrt{x}}=0[tex];</p>&#10;<p>[tex]18\sqrt{x}\neq 0[tex];</p>&#10;<p>x>0;</p>&#10;<p>[tex]12x+6x-36\sqrt{x}=0 ;

18x=36\sqrt{x}; 324{x}^{2}=1296x; x(324x-1296)=0; x=0, x=4; 

x=0-посторонний корень

остальное попозже напишу, щас посчитаю